Whose lives are they anyway? : the biopic as contemporary film genre - Bingham, Dennis, 1954- (ACLS Humanities E-Book., 2010)
Through detailed analyses and critiques of nearly twenty biopics, Whose Lives Are They Anyway? proves a critical point: The biopic is a genuine, dynamic genre and an important oneùit narrates, exhibits, and celebrates a subject's life and demonstrates, investigates, or questions his or her importance in the world; it illuminates the finer points of a personality; and, ultimately, it provides a medium for both artist and spectator to discover what it would be like to be that person, or a certain type of person.